Modeling of two-phase flow in boiling water reactor using phase-weighted ensemble average method - Aybar, Hikmet Ş.; Sharifpur, Mohsen (My University, 2009)
Investigations into boiling, the generation of vapor and the prediction of its behavior are important in the stability of boiling water reactors (BWR). The present models are limited to simplifications made to draw governing equations or lack of closure framework of the constitutive relations. The commercial codes fall into this category as well. Consequently, researchers cannot simply find the comprehensive updated relations before simplification in order to simplify them for their own works. This study offers a state of the art, phase-weighted, ensemble-averaged, twophase flow, two-fluid model for the simulation of two-phase flow with heat and mass transfer. This approach is then used for modeling the bulk boiling (thermal-hydraulic modeling) in BWR. The resultant approach is based on using the energy balance equation to find a relation Tor quality of vapor at any point. The equations are solved using SIMPLE algorithm in the finite volume method and the results compared with real BWR (PB2 BWR/4 NPP) and the boiling data. Comparison shows that the present model is satisfactorily improved in accuracy. © Shiraz University.
Keywords: Boiling; BWR; Heat and mass transfer; Two-fluid model; Two-phase flow